Genomics, Computational Biology and Drug Discovery for Mycobacterial Infections: Fighting the Emergence of Resistance - Munir, Asma; Vedithi, Sundeep Chaitanya; Chaplin, Amanda K.; Blundell, Tom L. (Frontiers in Genetics, 2020)
Tuberculosis (TB) and leprosy, mycobacterial infections caused by Mycobacterium tuberculosis and Mycobacterium leprae respectively, continue to be endemic in developing countries where the cost of new medicines presents major challenges and the situation is exacerbated by the emergence of resistance to many front-line antibiotics. A priority now is to design new antimycobacterials that are not only effective in combatting the diseases but are also less likely to give rise to resistance. In both these respects understanding the structure of drug targets in M. tuberculosis and M. leprae is a priority. In this review we describe structure-guided approaches to understanding the impacts of mutations that give rise to antimycobacterial resistance and the use of this information in the design of new medicines that are less susceptible to this challenge.